Phenylthiocarbamide taste perception as a possible genetic association marker for nutritional habits and obesity tendency of people - Dastan, Sevgi Durna; Degerli, Naci; Dastan, Taner; Yildiz, Fazilet; Yildir, Yavuz; Durna, Yusuf Muhammed; Karan, Tunay (Univ Karachi, 2015)
Ability to taste Phenylthiocarbamide (PTC) a bitter molecule, is usually used to know the heritable characteristic in both genetic and physiological studies. So far, no research has yet attested whether PTC blindness relation with obesity and some nutrition behaviors of human. This stu.dy is the first attempt on a large scale to examine PTC sensitivity in healthy and overweight people in Turkish population to define in the perception of bitter senses which is associated with nutrition habits, body mass index, age, gender, and to be in stable weight. PTC taste perception was measured by tasting PTC solution filtered in a paper. The results showed that tasters were significantly more frequent (81,8%) than nontasters (18,2%) in all population. A higher proportion of nontasters were observed in the quite fat individual group (BMI >= 40kg/m(2)). Alterations explained these differences in basic taste sensitivity, age, gender, BMI, individuals' family obesity situations, vegetarian nourishment. Increased frequency of nontasters allele is evident with obesity condition. This could be due to lack of preference for nutrition among nontasters. So the phenotypic variation in PTC sensitivity is genetic in origin; it may represent an association with obesity, dietary habits, regular weight, gender, and age.
Keywords: PTC taste sensitivity; obesity; taste genetics; nontaster PTC trait; food preference